Pertumbuhan Gunung Api Anak Krakatau setelah letusan katastrofi s 1883 - SUTAWIDJAJA, IGAN SUPRIATMAN (Geological Agency, 2006)
http://dx.doi.org/10.17014/ijog.vol1no3.20063Since its appearance in 1929, Anak Krakatau Volcano has been growing fastly. The elevation of Anak Krakatau Volcano from 1930 to 2005, within 75 years, has reached 315 m high. The growth rate is approximated to be four meters per year in average. Based on calculation, the volume of the body from the sea fl oor since 1927 until 1981 was 2.35 km3, and then in 1983 was 2.87 km3 and then in 1990 it reached 3.25 km3. The latest volume measurement in 2000, was 5.52 km3. Between 1992 up to 2001, within nine years, the eruption of Anak Krakatau took place almost every day, and it had caused its elevation to increase more than 100 m, and its area extent to become 378,527 m2. If the increase in height and the increase in volume are consistent, it is expected that in 2020, the volume of Anak Krakatauâ€™s edifi ce will proceed the volume of Rakata Volcano, Danan Volcano, and Perbuwatan Volcano (11.01 km3) shortly before catastrophic eruption in 1883. Since this volcano appeared above the sea level, the succession of vegetation never came up to a climax, except some of the species, such as Saccharum sp. and Casuarina sp. those are growing faster after the eruption stopped. The growth of coral reef on the lava fl ows that entered the sea about ten years ago, was much slower than those which are growing around the Rakata, Panjang and Sertung Islands. This case is probably due to the slow rate of cooling process of the lava fl ows, although the lava surfaces are blocky. Â